Relations of the Republic of Armenia with Georgia on the Eve of the Constantinople and Berlin Negotiations (May-June 1918) - Petrosyan, Gegham (YSU Journal of International Affairs, 2022)
The article examines in details the fact that on the eve of the negotiations of the countries of the Central Powers in Constantinople and Berlin, related to the republics of Transcaucasia, the relations of the Republic of Armenia with its direct neighbors, Georgia and Azerbaijan, were unstable, uncertain and contradictory, due to their different political goals, orientation and territoriality. Particular attention was paid to the fact that after gaining independence by the three peoples of Transcaucasia, a very favorable situation arose for Georgia and Azerbaijan. The direction of their foreign policy was also clear. Germany protected the interests of Georgia, and the Ottoman Turkey protected the interests of Azerbaijan, in both cases to the detriment of the Republic of Armenia.
Keywords: Republic of Armenia; Azerbaijan; Georgia; Ottoman Turkey; Germany; Russia; Batumi Pact; immediate neighbors; territorial disputes; favorable situation